Haemaphysalis calva Nuttall and Warburton 1915 - Petney, Trevor N.; Boulanger, Nathalie; Saijuntha, Weerachai; Chitimia-Dobler, Lidia; Pfeffer, Martin; Eamudomkarn, Chatanun; Andrews, Ross H.; Ahamad, Mariana; Putthasorn, Noppadon; Muders, Senta V.; Petney, David A.; Robbins, Richard G. (Zenodo, 2019)
Haemaphysalis calva Nuttall and Warburton, 1915 This is a rare Oriental species that has been recorded from peninsular Malaysia and Thailand, as well as Indonesia (Hoogstraal and Wassef 1981; Tanskul et al . 1983). It is a parasite predominantly of sambar deer, but has also been recorded from wild pig, palm civet, Himalayan brown bear ( Ursus arctos isabellinus ) and water buffalo (Hoogstraal and Wassef 1981). Adults and nymphs are described in Hoogstraal and Wassef (1981). Published as part of Petney, Trevor N., Boulanger, Nathalie, Saijuntha, Weerachai, Chitimia-Dobler, Lidia, Pfeffer, Martin, Eamudomkarn, Chatanun, Andrews, Ross H., Ahamad, Mariana, Putthasorn, Noppadon, Muders, Senta V., Petney, David A. & Robbins, Richard G., 2019, Ticks (Argasidae, Ixodidae) and tick-borne diseases of continental Southeast Asia, pp. 1-89 in Zootaxa 4558 (1) on page 23, DOI:10.11646/zootaxa.4558.1.1, http://zenodo.org/record/2613120